Urgensi Pemberian Kabar Gembira serta Ucapan Selamat atas Kelahiran Anak Perspektif Al-Qur’an dan Hadist - Ali Ridho; Ach. Mahfudz Abd. Qadir (LPPM STAI Ihyaul Ulum Gresik, 2020)
This research raises the importance of giving good news and congratulations on the birth of children, these two things besides the encouragement taught by God through the angels sent, namely Gabriel, Michael and Isrofil when giving good news and congratulations on the birth of his son Ishaq, also has a psychological impact on the parents of children born, namely self-confidence, trying to be better and of course, there will be a fabric of friendship. This research was conducted by examining a variety of literature relating to verses of the Koran and al-Hadith that explain about giving encouragement and congratulations on the birth of a child coupled with general references such as educational psychology. From the research conducted, it was suggested that the suggestion of giving encouraging news and saying goodbye to the birth of a child had a good effect on children's parents, namely trying to become better, more confident and intertwined with relationships.